Google meet usage for continuity and sustainability of online education during pandemic - Hasbullah, Nurul Haziqah; Rahmatullah, Bahbibi; Mohamad Rasli, Roznim; Khairudin, Moh; Downing, Kevin (Journal of ICT in Education, 2022)
This research analyzes the studies on using Google Meet to conduct online classes for educational sustainability purposes. When a series of lockdowns were implemented to handle the Covid-19 pandemic, all educational institutions were physically closed. This gives rise to the issues of continuity and sustainability of education. Teachers turned to online meeting applications to connect to students and ensure teaching and learning continue despite the physical school closure. Data for this research were taken from articles published in the Scopus database, starting from 2019; the start of the pandemic on a global scale. Thematic analysis resulted in four primary themes: students’ perception, teachers’ perception, teachers’ experience, and teaching and learning challenges. Both positive and negative points were uncovered regarding the use of Google Meet during the lockdown. This paper will help identify the benefits and challenges of Google Meet use and guide those attempting to improve their online learning experiences.